Analisis Studi Kasus Produk Indomie di Nigeria: Positioning, Promotion, dan Channel Management - Jamira, Anaseputri; Razi, Fachruddin (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research discusses an organization that is involved in global marketing, which focuses its resources on global market opportunities and threats. The research object is Indofood with its product Indomie. The problems discussed relate to Indofood's marketing strategy for Indomie brand noodle products in Nigeria, seen from how Indomie shapes perceptions in the minds of the Nigerian people (positioning), how Indomie carries out promotional activities in Nigeria to encourage sales, and how Indomie is distributed in various remote areas in Nigeria. This type of research is descriptive with case study research techniques, which uses primary and secondary data. Indomie in Nigeria has successfully dominated the market and continues to develop as the strongest instant noodle brand through the right combination of good product strategy and affordable prices, the right positioning, integrated promotions and aggressive distribution. The company is expected to continue to strengthen its business through creating competitive advantages. This research is specific, where it only focuses on a few small parts of marketing strategies or activities, which can be followed up and developed further in the future.